cGMP: Generators, Effectors and Therapeutic Implications - Schmidt, Harald H. H. W. (Springer, 2017)
After the discovery of endogenous NO formation in the late '80s and the 1998 Nobel Prize in Physiology or Medicine, many researchers and physicians again became interested in the NO/sGC interaction and cGMP-dependent signaling. This book is an enthusiastic celebration of cyclic guanosine monophosphate (cGMP) and amply illustrates the importance of this field of science to patients and the way in which the field has evolved. It is exclusively devoted to this exciting and important signaling molecule, addressing all recent advances in understanding guanylate cyclase regulation, NO/sGC interactions, cGMP effector mechanisms and their pathophysiological and pharmacological implications. Particular attention will also be given to clinical applications of the novel cGMP-elevating drugs which are on the horizon, thus spanning the continuum from basic science to clinic.